Risk factors for mortality in patients with acute leukemia and bloodstream infections in the era of multiresistance. - Carolina Garcia-Vidal; Celia Cardozo-Espinola; Pedro Puerta-Alcalde; Francesc Marco; Adrian Tellez; Daiana Agüero; Francisco Romero-Santana; Marina Díaz-Beyá; Eva Giné; Laura Morata; Olga Rodríguez-Núñez; Jose Antonio Martinez; et al. (PLoS ONE)
Objectives We assess the epidemiology and risk factors for mortality of bloodstream infection (BSI) in patients with acute leukemia (AL). Methods Prospectively collected data of a cohort study from July 2004 to February 2016. Multivariate analyses were performed. Results 589 episodes of BSI were documented in 357 AL patients, 55% caused by gram-positive bacteria (coagulase-negative staphylococci 35.7%, Enterococcus spp 10.8%) and 43.5% by gram-negative bacteria (E. coli 21%, PA 12%). We identified 110 (18.7%) multidrug-resistant (MDR) microorganisms, especially MDR-Pseudomonas aeruginosa (7%) and extended-spectrum beta-lactamase producing Enterobacteriaceae (7%). The 30-day mortality was 14.8%. Age (OR 3.1; 95% CI 1.7-5.7); chronic lung disease (4.8; 1.1-21.8); fatal prognosis according to McCabe index (13.9; 6.4-30.3); shock (3.8; 1.9-7.7); pulmonary infection (3.6; 1.3-9.9); and MDR-PA infections with inappropriate treatment (12.8; 4.1-40.5) were related to mortality. MDR-PA BSI was associated to prior antipseudomonal cephalosporin use (9.31; 4.38-19.79); current use of betalactams (2.01; 1.01-4.3); shock (2.63; 1.03-6.7) and pulmonary source of infection (9.6; 3.4-27.21). Conclusions MDR organisms were commonly isolated in BSI in AL. Inappropriate empiric antibiotic treatment for MDR-PA is the primary factor related to mortality that can be changed. New treatment strategies to improve the coverage of MDR-PA BSI should be considered in those patients with risk factors for this infection.